Produção e composição do leite de vacas das raças Holandês e Jersey, em pastagem de azevém anual - Diefenbach, Jairo (2012)
This study evaluated the lactation curve shape, the yield and composition of milk from cows of Holstein and Jersey breeds grazing annual ryegrass (Lolium multiflorum) in northwestern Rio Grande do Sul, and aimed to analyze its response when subjected to grazing pasture herd consisting of two genotypes. The experiment was conducted from 08.18.2010 to 10.29.2010 and are used in total, eleven tester cows of each racial group and a variable number of regulator cows. The animals were managed in rotational grazing with variable stocking rate and were supplemented at a rate of 1 kg per 3 liters of milk produced above 15 liters / cow / day. Pasture management allowed similar grazing conditions between the two tested breeds and proved to be not limiting to pasture and animals production. Individual milking performance was measured once a week throughout experimental period. The visual body condition score (BCS, 1-5), was also registered weekly, and body weigh was measured monthly. The experimental design for pasture variables and for individual animal production was a randomized block design with replications in time, having been used stepwise proc (SAS, 2009) to test regression models. Only the supplement in the months August, September and October in analysis, besides individual productions corrected to 4% fat, day consuption in the months of August, September and October was considered in analysis, besides individual animal productions corrected to 4% fat, days in lactation period , body weights, BCS, number of lactations and age. Individual samples were taken by milking in September and October, and analyzed for the following milk components: fat, protein, lactose, water, acidity, freezing point, density, and computed total dry extract (TDE) and defatted dry extract (DDE). The statistical analysis for milk components was randomized complete blocks with triple factorial arrangement for breeds (2), periods (2), and stages of lactation (4). ANOVA was performed by GLM (SAS, 2009) and multivariate analysis, through Software Multiv (Pillar, 1997), using the correlation between variables as a measure of similarity, and clustering criteria was the least variance of sum of squares Jersey exceeded Holstein (P <0.005) for fat (%) lactose (%) and protein (%); Holstein was exceeding Jersey (P <0.0001) for fat (kg), protein (kg) and TDE ( kg). Correlation studies showed a clear difference in the degree of association between genotypes for dry matter intake of feed, with lower association for Jersey genotype, Holtstein presented a higher and consistent dependence of intake throughout the experimental period, coinciding with pasture cycle. This trend may indicate greater efficiency of Jersey genotype in the use of pastures of high quality, obtained in the initial pasture phases. The regression studies indicated that supplement dry matter intake (partial R ²) in September explained 65.69% of milk production for Holstein breed, and supplement dry matter intake (partial R ²) in October explained 55.73% of milk production of Jersey breed.